Research into Machine Learning Algorithms for the Construction of Mathematical Models of Multimodal data Classification Problems - Бойко, Наталія; Boyko, Nataliya (Видавництво Львівської політехніки, 2021)
Сьогодні алгоритми машинного навчання (ML) все більше інтегруються у повсякденне життя. Можна навести безліч сфер сучасного життя, де вже застосовуються методи класифікації. Досліджуються методи, які враховують попередні передбачення та помилки, які обчислюються в результаті інтегрування даних задля отримання прогнозів, для отримання результату класифікації. Проведено загальний огляд методів класифікації. Здійснено експерименти над алгоритмами машинного навчання для мультимодальних даних. Важливо враховувати всі характеристики метрик та ознак під час використання алгоритмів ML для прогнозування мультимодальних даних. В роботі проаналізовано основні переваги та недоліки алгоритмів Gradient Boosting, Random Forest, Logistic Regression та XGBoost.

Currently, machine learning algorithms (ML) are increasingly integrated into everyday life. There are many areas of modern life where classification methods are already used. Methods taking into account previous predictions and errors that are calculated as a result of data integration to obtain forecasts for obtaining the classification result are investigated. A general overview of classification methods is conducted. Experiments on machine learning algorithms for multimodal data are performed. It is important to consider all the characteristics of metrics and features when using ML algorithms to predict multimodal data. The main advantages and disadvantages of Gradient Boosting, Random Forest, Logistic Regression and XGBoost algorithms are analyzed in the work.
Дослідження алгоритмів машинного навчання для побудови математичних моделей задач класифікації мультимодальних даних
Keywords: classification; binary classification; gradient boosting; random forest; logistic regression; X